Who's up to the challenge? 70

Calculus Level 5

0 x ln x 1 + e x d x = 1 B π C π D ln A + π E ln F G + π H ln π I \large \int _{ 0 }^{ \infty }{ \dfrac { x\ln { x } }{ 1+{ e }^{ x } } \, dx } =\dfrac { 1 }{ B } \pi ^{ C }-{ \pi }^{ D }\ln { A } +\dfrac { { \pi }^{ E }\ln { F } }{ G } +\dfrac { { \pi }^{ H }\ln { \pi } }{ I }

The equation above holds true for positive integers B , C , D , F , G , H B,C,D,F,G,H and I I such that F F is minimized.

Find B + C + D + E + F + G + H + I B+C+D+E+F+G+H+I .

Notation : A A denotes the Glaisher–Kinkelin constant , A 1.2824 A \approx 1.2824 .


The answer is 40.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We know , L i s ( 1 ) = 1 Γ ( s ) 0 x s 1 e x + 1 d x \displaystyle -Li_{s}(-1) = \frac{1}{\Gamma(s)}\int_{0}^{\infty} \frac{x^{s-1}}{e^x+1}dx

So if G ( s ) = 0 x s 1 e x + 1 d x \displaystyle G(s)=\int_{0}^{\infty} \frac{x^{s-1}}{e^x+1}dx then our target integral is G ( 2 ) G'(2)

G ( s ) = L i s ( 1 ) Γ ( s ) = η ( s ) Γ ( s ) \displaystyle G(s) = -Li_{s}(-1)\Gamma(s) = \eta(s)\Gamma(s) , Since by definition of polygarithm we see L i s ( 1 ) = n = 1 ( 1 ) n 1 n s = η ( s ) \displaystyle -Li_{s}(-1)=\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{n^s} = \eta(s)

Since η ( s ) = ( 1 2 1 s ) ζ ( s ) \displaystyle\eta(s)=(1-2^{1-s})\zeta(s) & Γ ( s ) = Γ ( s ) ψ 0 ( s ) = Γ ( s ) ( H s 1 γ ) \displaystyle \Gamma'(s)=\Gamma(s)\psi_{0}(s)=\Gamma(s)(H_{s-1}-\gamma) we have,

G ( 2 ) = Γ ( 2 ) η ( 2 ) + η ( 2 ) Γ ( 2 ) = η ( 2 ) + π 2 12 ( 1 γ ) \displaystyle G'(2) = \Gamma(2)\eta'(2) + \eta(2)\Gamma'(2) = \eta'(2) + \frac{\pi^2}{12}(1-\gamma)

η ( s ) = ζ ( s ) ( 1 2 1 s ) + 2 1 s ln 2 ζ ( s ) \displaystyle \eta'(s) = \zeta'(s)(1-2^{1-s}) + 2^{1-s}\ln2\zeta(s)

η ( 2 ) = π 2 12 γ + π 2 ln π 12 + π 2 ln 2 6 π 2 ln A \displaystyle \eta'(2) = \frac{\pi^2}{12}\gamma + \frac{\pi^2 \ln\pi}{12} + \frac{\pi^2 \ln2}{6} - \pi^2 \ln A

So we have G ( 2 ) = π 2 12 + π 2 ln π 12 + π 2 ln 2 6 π 2 ln A \displaystyle G'(2) = \frac{\pi^2}{12} + \frac{\pi^2 \ln\pi}{12} + \frac{\pi^2 \ln2}{6} - \pi^2 \ln A

So the answer is : 12 + 2 + 2 + 12 + 2 + 2 + 6 + 2 = 40 \boxed{12+2+2+12+2+2+6+2=40}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...